2001
DOI: 10.1038/sj.bjp.0704278
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of agonism at G‐protein coupled receptors by phosphatidic acid and lysophosphatidic acid in human embryonic kidney 293 cells

Abstract: Several di erent molecular species of phosphatidic acid (PA) bind to a G-protein coupled receptor (GPCR) to induce activation of the p42/p44 mitogen-activated protein kinase (p42/p44 MAPK) pathway in HEK 293 cells. PA is active at low nanomolar concentrations and the response is sensitive to pertussis toxin (which uncouples GPCRs from G i/o ). The de-acylated product of PA, lysophosphatidic acid (LPA), which binds to members of the endothelial di erentiation gene (EDG) family of receptors also stimulated p42/p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 12 publications
3
18
0
Order By: Relevance
“…Finally, to determine that the changes in ceramide synthesis in cultured cells were not due to the conversion of FTY720 to FTY720-P (9), which could bind to an S1PR at the cell surface and thus influence ceramide synthesis, we examined the effect of FTY720 in the presence of suramin, an inhibitor of G-protein-coupled receptors (31). No changes were observed in ceramide synthesis after incubation with FTY720 in the absence or presence of suramin (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, to determine that the changes in ceramide synthesis in cultured cells were not due to the conversion of FTY720 to FTY720-P (9), which could bind to an S1PR at the cell surface and thus influence ceramide synthesis, we examined the effect of FTY720 in the presence of suramin, an inhibitor of G-protein-coupled receptors (31). No changes were observed in ceramide synthesis after incubation with FTY720 in the absence or presence of suramin (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Accordingly, HEK293T cells were transfected with an expression plasmid encoding for an EE-tagged P-Rex1 and stimulated via their endogenous LPA and ␤-adrenergic receptors, which can couple to G i and G s , respectively (35)(36)(37). The data presented in Fig.…”
Section: Phosphorylation Of P-rex1 By Pka-when Incubated With [␥-mentioning
confidence: 99%
“…It has, for example, been reported to be involved in membrane recruitment of Raf-1, which contains a specific PA binding region [Rizzo et al, 2000]. Besides its action as intracellular second messenger studies suggested that PA may signal via cell surface GPCRs either in the micromolar [Sliva et al, 2000] or nanomolar concentration range [Alderton et al, 2001]. Alderton et al [2001] have shown that PA and related molecular species such as doPA activate, via a Ga i/o -dependent mechanism, the p42/44 mitogen-activated protein kinase (MAPK) pathway in HEK293 cells.…”
Section: Gpcrs For Pamentioning
confidence: 99%
“…Besides its action as intracellular second messenger studies suggested that PA may signal via cell surface GPCRs either in the micromolar [Sliva et al, 2000] or nanomolar concentration range [Alderton et al, 2001]. Alderton et al [2001] have shown that PA and related molecular species such as doPA activate, via a Ga i/o -dependent mechanism, the p42/44 mitogen-activated protein kinase (MAPK) pathway in HEK293 cells. They suggested GPR45 to be a possible candidate but did not test PA for functional activity on GPR45 in this report.…”
Section: Gpcrs For Pamentioning
confidence: 99%
See 1 more Smart Citation